Understanding the Needs of Patients’ Families in the Intensive Care Unit: A Comprehensive Literature Review - Hafifah, Ifa; Rahmi, Siti; Nasution, Tina Handayani (STIKep PPNI Jawa Barat, 2025)
Aims: Families of patients in intensive care units (ICUs) face significant psychological and emotional challenges, with diverse needs spanning assurance, information, proximity, support, and comfort. Understanding and addressing these needs is crucial for enhancing family well-being and satisfaction with ICU care. Objective: This study aims to synthesize existing evidence on the needs of ICU patients’ families, identify priority domains, and explore factors influencing these needs. Methods: A systematic literature review was conducted following PRISMA guidelines. Searches across PubMed, Scopus, CINAHL, Web of Science, and PsycINFO identified studies published between January 2015 and December 2024. Inclusion criteria focused on peer-reviewed articles addressing the emotional, informational, or practical needs of ICU patients’ families. Data extraction and quality assessment were performed using the Joanna Briggs Institute Critical Appraisal Tools. Thematic synthesis was applied for qualitative data, while quantitative findings were analyzed descriptively. Results: From 11 studies, assurance emerged as the most critical need across diverse populations, followed by information, proximity, support, and comfort. Sociodemographic factors such as age, education level, and gender, as well as contextual factors like cultural norms and length of ICU stay, significantly influenced family needs. Assurance and information were universally prioritized, while proximity and support varied based on regional and cultural contexts. Conclusion: ICU families’ needs are multidimensional and influenced by individual, clinical, and sociocultural factors. Assurance and information consistently rank as top priorities, highlighting the need for family-centered, culturally sensitive care strategies. Tailored interventions, effective communication, and policies facilitating family presence can address these needs and improve family satisfaction. Future research should explore real-time strategies and the role of technology in meeting family needs.